2015
DOI: 10.1002/adma.201501217
|View full text |Cite
|
Sign up to set email alerts
|

Tungsten Oxides for Photocatalysis, Electrochemistry, and Phototherapy

Abstract: The conversion, storage, and utilization of renewable energy have all become more important than ever before as a response to ever-growing energy and environment concerns. The performance of energy-related technologies strongly relies on the structure and property of the material used. The earth-abundant family of tungsten oxides (WOx ≤3 ) receives considerable attention in photocatalysis, electrochemistry, and phototherapy due to their highly tunable structures and unique physicochemical properties. Great bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
320
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 525 publications
(326 citation statements)
references
References 172 publications
(226 reference statements)
4
320
0
2
Order By: Relevance
“…Moreover, surface OVs can enhance the electron transfer from O-vacancies to metal d band to further effectively tune the adsorption of surface species for catalysis. [40][41][42] For example, Chen et al investigated the influence of OVs on the oxygen electrocatalysis of rutile-type β-MnO 2 by introducing intrinsic OVs without modification by foreign additives. [42] They found that OVs-containing oxide demonstrates a more positive potential, larger current and lower peroxide production for ORR catalysis, and also promotes OER catalysis.…”
Section: Defect Engineeringmentioning
confidence: 99%
“…Moreover, surface OVs can enhance the electron transfer from O-vacancies to metal d band to further effectively tune the adsorption of surface species for catalysis. [40][41][42] For example, Chen et al investigated the influence of OVs on the oxygen electrocatalysis of rutile-type β-MnO 2 by introducing intrinsic OVs without modification by foreign additives. [42] They found that OVs-containing oxide demonstrates a more positive potential, larger current and lower peroxide production for ORR catalysis, and also promotes OER catalysis.…”
Section: Defect Engineeringmentioning
confidence: 99%
“…1−4 However, precedent research conducted on the tungsten trioxide systems is mainly focused on the most stable phase at room temperature, namely, the monoclinic phase (γ-WO 3 ), and its doped systems. 5,6 The metastable hexagonal tungsten trioxide (h-WO 3 ), though chemically similar to the monoclinic phase, has a rather unique crystal structure with empty hexagonal and trigonal nanochannels in a framework of vertex-shared WO 6 octahedrons. 7,8 This phase has been found to be stabilized under specific synthesis conditions, e.g., by controlling the ligands or intercalating different kinds of alkali-metal ions, 9 and this stabilization effect has also been investigated theoretically.…”
Section: Introductionmentioning
confidence: 99%
“…These capabilities have enabled significant progress for Fe 2 O 3 , [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] Cu 2 O, [27][28][29][30] and other photoelectrodes. [6,31,32] There is a significant design advantage to using composite host-guest nanostructures for light-harvesting materials with low carrier mobilities. In this design, a "host" scaffold transports majority carriers to the substrate and the "guest" absorber transports minority carriers to the water/catalyst interface.…”
Section: Introductionmentioning
confidence: 99%